2022
DOI: 10.1097/mcd.0000000000000411
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic studies of thiamine metabolism dysfunction syndrome-4: case series and review of the literature

Abstract: Thiamine metabolism dysfunction syndrome-4 (THMD-4) is an autosomal recessive inherited rare disease (OMIM #613710) characterized by febrile illness associated episodic encephalopathy, leading to transient neurological dysfunction and progressive polyneuropathy. We report three patients from two different families with normal development, episodic encephalopathy, gait disorder, progressive chronic polyneuropathy characterized by motor difficulties, distal weakness, and hoarseness (dysphonia). We identified a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Patients usually recover completely after attacks or resolution of the precipitating factors, while some patients may have mild residual weakness. The incidence of the disease is very rare (<1 in 1,000,000) with very few cases having been reported, resulting in difficulty with clinically recognizing the disease (2). We report a case of an 8-year-old boy with THMD-4 who presented with clinical features and imaging findings characteristic of the disease but with absence of altered sensorium, further confirmed by genetic testing.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Patients usually recover completely after attacks or resolution of the precipitating factors, while some patients may have mild residual weakness. The incidence of the disease is very rare (<1 in 1,000,000) with very few cases having been reported, resulting in difficulty with clinically recognizing the disease (2). We report a case of an 8-year-old boy with THMD-4 who presented with clinical features and imaging findings characteristic of the disease but with absence of altered sensorium, further confirmed by genetic testing.…”
Section: Introductionmentioning
confidence: 82%
“…Nerve conduction studies showed motor/sensory axonal polyneuropathy. Treatment with thiamine supplementation at 400mg/day usually relieves the symptoms and needs to be continued lifelong to prevent metabolic decompensation and recurrences (2,12). Early recognition of the disease and treatment with vitamin supplementation yields better clinical outcomes, with complete recovery or residual distal myasthenia and cognitive delay (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation